Development of Fiqh Learning Based on Islamic Boarding Schools MA KMM Kauman Padang Panjang West Sumatra - In'ami, Moh; D, Derliana; Vestia, Etika; Setiawan, Ade (Pascasarjana IAIN Kudus, 2022)
Learning of Fiqh, in general, has not been able to strengthen the characteristics of Islamic boarding school. Besides, learning of Fiqh in particular, has other significant problems: a) The number of teaching hours for Fiqh based on Islamic boarding school is insufficient); b) Reference books based on Islamic boarding school has not been used and utilized); c) There are no examples of integrated learning between madrasah and Islamic boarding schools, and d) There are not many graduates who continue their studies at university majoring in religion. This research aims to produce an example for learning of Fiqh based on Islamic boarding schools that can be implemented classically in classroom and halaqah in dormitories of MA KMM Kauman Padang Panjang. In order to achieve this goal, the author uses a Research and Development (R&D) development model. Which is well-known as a 4D development model. In practice, this development model consists of several stages, define, design, develop, and disseminate.